Breed variability in the cellular mediated immune response to experimental Neospora caninum infection in heifers - Fiorani, Franco (2024)
Protozoan parasite Neospora caninum causes abortion in infected cattle while others remain asymptomatic. Host immunity plays a critical role in the outcome of bovine neosporosis. Despite extensive research, there is a critical gap in therapeutic and preventive measures, and no effective vaccines are available. Both beef and dairy cattle can suffer from N. caninum-induced abortions, but cumulative evidence suggests a breed susceptibility being higher in dairy compared with beef breeds. It has been established that the response to N. caninum infection primarily involves a cell-mediated immune response (CMIR) regulated by T-helper type 1 (Th1) cells and specific cytokines. The delayed-type hypersensitivity (DTH) skin test has been used to measure the ability of livestock to generate CMIR, in the context of breeding for disease resistance and as a method for diagnosis of several diseases. In this study, we evaluated the immune response triggered by an N. caninum-induced DTH skin test between Holstein – a dairy breed intensively selected- and Argentinean Creole heifers – a beef breed with minimal genetic selection- to assess differences in CMIR following experimental N. caninum infection. The immune response, measured through skinfold thickness and histological and immune molecular analysis, revealed variations between the breeds. Our study found an increased CMIR in Argentinean Creole heifers compared to Holstein heifers. Differential gene expression of key cytokines was observed at the DTH skin test site. Argentinean Creole heifers exhibited elevated IFN-γ, IL-12, IL-10, and IL-4, while Holstein heifers only showed higher expression of IL-17. This finding could underscore genetic diversity in response to neosporosis, which could be used in breeding cattle strategies for disease resistance in cattle populations.